PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH BANK RAKYAT INDONESIA CABANG JAKARTA SUNTER - Nino Nopriandi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This research aims to obtain both factual and conceptual information about the effect of product quality and service quality on customer satisfaction at the Jakarta Branch BRI (Bank Rakyat Indonesia) Sunter. This research used observation or survey technique by using a questionnaire to measure customer’s satisfaction. The sampling method used Probability Sampling with participation of 100 customers as the respondents. The results of this research are simultaneous, both product quality and service quality do have a positive, relatively strong and significant effect on customer satisfaction by 62%. The remaining 38% are influenced by other variables outside the model. Partially the product quality has a strong and positive effect on customer satisfaction by 57% while partially the service quality has a strong, positive, and significant effect on satisfaction by 59%.